The Mick. The complete first season [videorecording (DVD)] - Olson, Kaitlin; Black-D'elia, Sofia; Jiménez, Carla; Barbusca, Thomas (20th Century Fox Home Entertainment, 2018)
A no-holds-barred comedy that gives new meaning to the phrase dysfunctional family. Mickey is an unapologetic degenerate, who suddenly finds herself stuck in affluent Greenwich, CT, raising her spoiled niece and nephews. She may discover it₂s not the buzzkill she always thought it would be.